Changes in winter stationary wave activity during weak mid‐latitude and Arctic thermal contrast period. (7th October 2019) - Wang, Sai; Nath, Debashis; Chen, Wen; Wang, Lin
Abstract: Using reanalysis data set, this study investigates the changes in winter mean stationary wave activity, when the thermal contrast between mid‐latitude and Arctic is weak. The mid‐latitude and Arctic thermal contrast was stronger during 1986–2003 and weaker during 1966–1985 and 2004–2017. The changes in stationary wave characteristics are studied based on the stationary wave activity flux (SWAF). Compare to the period when the contrast was stronger (1986–2003), both the convergence of SWAF and stationary wave amplitude have been enhanced in the Northern part of Eurasia during the periods 1966–1985 and 2004–2017. We further proposed that a weak mid‐latitude/Arctic thermal contrast provides a good condition for the enhancement of the stationary wave activity. The weak mid‐latitude‐Arctic thermal contrast is conducive to the enhancement of blocking frequency around Ural Mountains, which may contribute partly to the increase in stationary wave amplitude and associated changes in the SWAF. Furthermore, the weak thermal contrast is associated with the decrease in baroclinicity and synoptic‐scale eddy activity, which in turn contributes to the generation of stationary waves via eddy feedback processes. Abstract : Time series of regional mean winter temperature anomalies (unit: °C) over the (a) Arctic (black lines) and (b) mid‐latitudes (black lines). Time series of normalized winter temperature anomalies over the (c) Arctic (black lines) and (d) mid‐latitudes (black lines). The red lines in (a), (b) denote the mid‐latitude/Arctic temperature contrast calculated with the raw temperature anomalies. The red lines in (c), (d) denote the mid‐latitude/Arctic temperature contrast calculated with the normalized temperature anomalies. The results are based on the NCEP/NCAR reanalysis data set.